2012
DOI: 10.5137/1019-5149.jtn.6706-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of erbb2 in adamantinomatous craniopharyngiomas: a possible target for immunotherapy

Abstract: AIm:To determine the immunohistochemical expression of ErbB2 in adamantinomatous craniopharyngiomas (ACP) and to assess its relationship with nuclear expression of β-catenin in surgically resected human ACP tissue sections and to estimate whether these tumors could be candidates for anti-ErbB2 therapy. mAterIAl and methOds: The ErbB2 and β-catenin immunostaining was performed on paraffin embedded tissue sections of 20 ACP using avidin-biotin-peroxidase complex method. ErbB2 immunoreactivity was interpreted acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Other malignant solid tumors with HER2 overexpression include ovarian cancer, non small cell lung cancer, prostate cancer, gastric cancer, colorectal cancer, renal cell carcinoma, and bladder cancer (4)(5)(6). HER2 is a significant target for cancer therapy (7)(8)(9)(10). Herceptin (trastuzumab) is a humanized monoclonal antibody targeting HER2 and is widely used for the treatment of HER2-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other malignant solid tumors with HER2 overexpression include ovarian cancer, non small cell lung cancer, prostate cancer, gastric cancer, colorectal cancer, renal cell carcinoma, and bladder cancer (4)(5)(6). HER2 is a significant target for cancer therapy (7)(8)(9)(10). Herceptin (trastuzumab) is a humanized monoclonal antibody targeting HER2 and is widely used for the treatment of HER2-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,12,24,28,38 As a result of this mechanism, nuclear accumulation of b-catenin is a histological hallmark of CTNNB1 mutation. 10,12,16,26,41 In the case of craniopharyngiomas, mutation of CTNNB1 has been described in 69%-100% 9,20,28 of ACP specimens, while it is not routinely observed in PCP or other parasellar tumors. 9,28 In the most detailed study to date, CTNNB1 mutation was identified in 95% of ACP specimens, using massively parallel sequencing and targeted genotyping.…”
Section: Ctnnb1 Mutationmentioning
confidence: 99%
“…10,32 This protein plays a critical role in development, cellular proliferation, differentiation, and cell migration. 10,11,16,41 A destruction complex restrains b-catenin within the cytosol and facilitates its ubiquitination and proteasomal degradation. 31 The Wnt protein family includes approximately 20 different proteins that bind to the Frizzled (Fz) family of receptors.…”
mentioning
confidence: 99%
“…Mutation in exon 3 of CTNNB1, leading to overactivation of the Wnt/b-catenin signaling pathway, is considered the main oncogenic driver of ACP tumorigenesis. Moreover, other pathways, such as ERBB2 and SHH signaling, have also been shown to be related to tumor growth and proliferation (6)(7)(8). Gaston et al constructed an ACP embryonic and inducible model to further confirm that cells in the b-catenin-accumulating cluster promote tumor growth by regulating paracrine cells with a series of related proteins, including bone morphogenic proteins (BMPs) and fibroblast growth factors (FGFs) (9,10).…”
Section: Introductionmentioning
confidence: 99%